Perceptions, Attitudes, Learning, and Challenges of Social Work Undergraduates in Cultivation of International Talent: A Survey of Five Universities in Guangzhou, China - Feiping, Ning; Yahaya, Mohd Haizzan Bin (Asian Social Work Journal, 2025)
In 2019, China's Guangdong-Hong Kong-Macao Greater Bay Area proposed the establishment of an international education demonstration area. As the core city of the Greater Bay Area, major universities in Guangzhou have initiated initiatives to cultivate international talent. This study aims to evaluate the knowledge, attitudes, and internationalized learning of undergraduate social work students, as well as the challenges they encounter in cultivating international talents within their majors at Guangzhou universities. In this study, 291 online questionnaire data from undergraduate students from five universities in Guangzhou were collected through a questionnaire survey. The collected data were analysed using descriptive statistics, the chi-square test, and one-way ANOVA. The results showed that students value most is to master professional knowledge in international social work. Most of the students (86.6%) believed that it was necessary to cultivate international talents in social work, but 19.3% of the students believed that the prospect was not optimistic, and 24.1% of the students held a wait-and-see attitude. The gender of the students had a significant effect on attitudes. There were significant differences in students' internationalization learning among universities. Challenges faced by students are centered on the unfulfilled demand for internationalized learning. Although most universities have put forward the goal of cultivating international talent, there is still a gap between the goal and its achievement. It is recommended that universities increase resources for social work majors and improve the internationalization level of teachers to achieve the goal of cultivating international social work talents.